2021
DOI: 10.28948/ngumuh.754411
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study for artificial neural network (ANN) based prediction of electric energy production of diesel engine based cogeneration power plant

Abstract: In this study artificial neural network (ANN) has been developed in order to estimate the electricity production of cogeneration power plant, which produces a total of 11.52 MW electric power, consisting of two V type and 12 cylinders each of which is 5.760 kW diesel engines running with heavy fuel oil no 6. In the ANN which was developed for the estimation of electric power generation of cogeneration, power plant(W), Time period (t), working hours (h), fuel consumption (m) and internal power consumption (Wp) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Recent progress in the data analysis and computer science areas resulted in implementing statistical 40 and machine learning 41,42 techniques in various fields, mainly in vision‐based learning, 43 energy storage 44 and management, 45 and material design 46 and characterization. Moreover, it is possible to develop machine learning methods utilizing extracted/selected features to enhance the prediction accuracy 47 .…”
Section: Methodsmentioning
confidence: 99%
“…Recent progress in the data analysis and computer science areas resulted in implementing statistical 40 and machine learning 41,42 techniques in various fields, mainly in vision‐based learning, 43 energy storage 44 and management, 45 and material design 46 and characterization. Moreover, it is possible to develop machine learning methods utilizing extracted/selected features to enhance the prediction accuracy 47 .…”
Section: Methodsmentioning
confidence: 99%
“…ANN models, which have higher performance compared to traditional simulation methods, are often preferred 22 . It can be shown that the ANN model is effective and also applied in scientific studies conducted in different fields such as energy, 23 electronic, 24 nanotechnology, 25 construction 26 and medicine 27 …”
Section: Introductionmentioning
confidence: 99%
“…21 ANN models, which have higher performance compared to traditional simulation methods, are often preferred. 22 It can be shown that the ANN model is effective and also applied in scientific studies conducted in different fields such as energy, 23 electronic, 24 nanotechnology, 25 construction 26 and medicine. 27 Liu et al 28 suggested an ANN model for mean function and reliability estimation in the Wiener process for failure modeling and reliability estimation.…”
Section: Introductionmentioning
confidence: 99%